The Use of Laparoscopy Simulation to Explore Gender Differences in Resident Surgical Confidence - Rebecca L. Flyckt; Eliza E. White; Linnea R. Goodman; Catherine Mohr; Sanjeev Dutta; Kristine M. Zanotti (Hindawi Limited, 2017)
Background. The objective of this study was to determine whether female surgical residents underestimate their surgical abilities relative to males on a standardized test of laparoscopic skill. Methods. Twenty-six male and female general surgery residents and 25 female obstetrics and gynecology residents at two academic centers were asked to predict their score prior to undergoing the Fundamentals of Laparoscopic Surgery standardized skills exam. Actual and predicted score as well as delta values (predicted score minus actual score) were compared between residents. Multivariate linear regression was used to determine variables associated with predicted score, actual score, and delta scores. Results. There was no difference in actual score based on residency or gender. Predicted scores, however, were significantly lower in female versus male general surgery residents (25.8 ± 13.3 versus 56.0 ± 16.0; p<0.01) and in female obstetrics and gynecology residents versus male general surgery residents (mean difference 20.9, 95% CI 11.6-34.8; p<0.01). Male residents more accurately predicted their scores while female residents significantly underestimated their scores. Conclusion. Gender differences in estimating surgical ability exist that do not reflect actual differences in performance. This finding needs to be considered when structuring mentorship in surgical training programs.